PENCATATAN PEMBUKUAN SEDERHANA UNTUK PELAKU UKM ANGGOTA KOPERASI USAHA BERSAMA KEPANJEN MALANG - Sungkawati, Endang; Ratnawati, '; Hendrawaty, Rina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
The public interest to establish SMEs continue to increase, but many of them do not have the ability to manage finances. Knowledge of financial analysis , particularly for business activity is necessary, because with such knowledge of SMEs will be able to book their business finances and be able to distinguish business finance , venture capital , as well as personal finances . This was the case in the SMEs that are members of cooperatives (Kop - Uber) Talangagung District of Malang. SMEs are generally not have the knowledge and the ability to record and analyze the effort. So that they find it difficult to meet its obligations as a member of the cooperative. Therefore, there should be training and mentoring members of the financial analysis for Kop - Uber. Training and assistance was done on two groups of SMEs as Partners.This activity istransfer knowledge of financial analysis for the group of partners who are members of Kop - Uber. After training and mentoring, participants gain knowledge of : (1) how to perform financial analysis efforts, (2) is able to record financial matters related to its business , among others, are able to make cash flow, balance sheet , income statement , classifying the various types of costs, and calculate the cost of production. (3) the analysis of bookkeeping, is expected to analyze the advantages and disadvantages of business, and thus the expected participation of the cooperatives are becoming increasingly active and flowing. (4) Furthermore, participants are trained to analyze the business, financial record attempt, it is expected that trainees can pass on their knowledge to other members